Education, Employment and Utilization Patterns of French-Canadian and English-Canadian Engineering Graduates - Gross, Andrew C. (Relations industrielles / Industrial Relations, 1969)
In this article, the author compares the experience of French-speaking and English-speaking engineering graduates in Canada, focusing on similarities and differences in their education, employment and utilization patterns. This essay is based on a larger study which has dealt with engineering manpower in Canada.